Therapeutic Approaches for Treating Pulmonary Arterial Hypertension by Correcting Imbalanced TGF-β Superfamily Signaling - Andre, Patrick; Joshi, Sachindra R.; Briscoe, Steven D.; Alexander, Mark J.; Li, Gang; Kumar, Ravindra (Frontiers in Medicine, 2022)
Pulmonary arterial hypertension (PAH) is a rare disease characterized by high blood pressure in the pulmonary circulation driven by pathological remodeling of distal pulmonary arteries, leading typically to death by right ventricular failure. Available treatments improve physical activity and slow disease progression, but they act primarily as vasodilators and have limited effects on the biological cause of the disease—the uncontrolled proliferation of vascular endothelial and smooth muscle cells. Imbalanced signaling by the transforming growth factor-β (TGF-β) superfamily contributes extensively to dysregulated vascular cell proliferation in PAH, with overactive pro-proliferative SMAD2/3 signaling occurring alongside deficient antiproliferative SMAD1/5/8 signaling. We review the TGF-β superfamily mechanisms underlying PAH pathogenesis, superfamily interactions with inflammation and mechanobiological forces, and therapeutic strategies under development that aim to restore SMAD signaling balance in the diseased pulmonary arterial vessels. These strategies could potentially reverse pulmonary arterial remodeling in PAH by targeting causative mechanisms and therefore hold significant promise for the PAH patient population.